2016
DOI: 10.14740/jocmr2411w
|View full text |Cite
|
Sign up to set email alerts
|

An Insight Into the Immunologic Events and Risk Assessment in Renal Transplantation

Abstract: Organ transplantation has always been considered to be the optimal therapeutic intervention in patients with end-stage organ failure. In the US, approximately 615,000 patients are diagnosed with end-stage renal disease and less than 30% have received a kidney transplant. One of the crucial drawbacks in successful renal transplantation is allograft rejection. Survival rates among transplant recipients have greatly improved due to better understanding of transplant biology and more effective immunosuppressive ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…However, the modest improvement of long‐term graft survival over the last decades remains a major concern in the transplant community . Accordingly, novel noninvasive biomarkers that might be of predictive value for assessing long‐term graft survival are currently being intensively investigated . By implementing HLA matching in transplant allocation systems, the transplant field has been among the first to achieve translation of genetic information into improved clinical outcomes through personalized medicine .…”
Section: Introductionmentioning
confidence: 99%
“…However, the modest improvement of long‐term graft survival over the last decades remains a major concern in the transplant community . Accordingly, novel noninvasive biomarkers that might be of predictive value for assessing long‐term graft survival are currently being intensively investigated . By implementing HLA matching in transplant allocation systems, the transplant field has been among the first to achieve translation of genetic information into improved clinical outcomes through personalized medicine .…”
Section: Introductionmentioning
confidence: 99%
“… 10 Immunosuppressants are usually used in clinical practice to reduce the risk of postoperative rejection. 11 However, long-term use of immunosuppressants can cause side effects, including inhibition of immune functions and adverse drug reactions.…”
Section: Introductionmentioning
confidence: 99%
“…They can bind to the mRNAs of their target genes in a sequence-specific manner, resulting in degradation of the mRNA or inhibition of translation; therefore, miRNAs have important roles in biological development, cell differentiation, cell apoptosis and tumor development. 12–14 Although studies have confirmed the roles of miRNAs in human organ transplantation, 11–13 there are few reports on miRNAs directly associated with corneal transplantation rejection. miR-466 and miR-184 are reported to be closely related with corneal lymphangiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNA), a class of small ncRNAs of approximately 21-24 nucleotides (nt) in length [98,99], have been shown to play different roles in human organ transplantations [100,101]. However, there are only a few reports on miRNAs being directly associated with corneal transplant rejection.…”
Section: Non-coding Rnas In Lymphangiogenesismentioning
confidence: 99%